Samoa : Staff Report of the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2005 Article IV Consultation for Samoa reports that the combination of sound economic management and structural reform had led to robust growth, low inflation, sound public finances, and a comfortable external position. With continued commitment to sound macroeconomic and reform policies, Samoa became one of the best managed economies in the Pacific Island region. The level of public debt has steadily declined from more than 90 percent to about 50 percent. Samoa also made progress toward the Millennium Development Goals.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet